78.0k views
1 vote
Y/m + y- 1/n = y-2/mn

slove for y

2 Answers

2 votes

Answer:

hello : y = ( n + m - 1 )/( m - 2 ) if : m - 2 ≠ 0

Explanation:

y/m + (y- 1)/n = (y-2)/mn

(ny+my - m)/mn = (y-2)/mn

ny+my - m = y - 2

ny+my - y = m - 2

( n + m - 1 )y = m - 2

y = ( n + m - 1 )/( m - 2 ) if : m - 2 ≠ 0

User Sebastian Farham
by
6.5k points
4 votes

Answer:

y = (m - 2) / (n + m - 1) .

Explanation:

y/m + y- 1/n = y-2/mn

Multiply through by the LCM mn:

yn + m(y - 1) = y - 2

yn + my - m = y - 2

yn + ym - y = m - 2

y(n + m - 1) = m - 2

y = (m - 2) / (n + m - 1) Answer.



User Teerapap
by
6.3k points